2015
DOI: 10.1039/c5ra12742d
|View full text |Cite
|
Sign up to set email alerts
|

Palladacycles derived from arylphosphinamides for mild Suzuki–Miyaura cross-couplings

Abstract: We present a type of palladacyclic complexes derived from arylphosphinamides which can be used as efficient and versatile precatalysts for mild Suzuki-Miyaura cross-coupling. With the presence of 1.0 mol% of palladacycles, a wide variety of aryl bromides and boronic acids could be coupled very efficiently at ambient temperature and under air atmosphere without the need of external supporting ligands. Moreover, the mild conditions also allow for smooth coupling of electron-deficient, i.e., the less stable aryl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Accordingly, we shifted our focus to a phosphinamide-based palladacycle catalyst 16, which was developed previously by our group (Du et al., 2015, Guan et al., 2014). A supportive clue, albeit not tightly related with the proposed Heck-type reaction, that encouraged us to inspect this catalyst herein is that 16 exhibited extremely high catalytic activity for mild Suzuki coupling of a broad range of arene ( pseudo )halides (Wu et al., 2015, Wu et al., 2018, Cao et al., 2018). To our delight, the use of 16 as catalyst did improve substantially the yield of 15a to 72% (entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, we shifted our focus to a phosphinamide-based palladacycle catalyst 16, which was developed previously by our group (Du et al., 2015, Guan et al., 2014). A supportive clue, albeit not tightly related with the proposed Heck-type reaction, that encouraged us to inspect this catalyst herein is that 16 exhibited extremely high catalytic activity for mild Suzuki coupling of a broad range of arene ( pseudo )halides (Wu et al., 2015, Wu et al., 2018, Cao et al., 2018). To our delight, the use of 16 as catalyst did improve substantially the yield of 15a to 72% (entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…To compare with the prior literature 27 – 31 , the low coupling efficiency is probably due to the excessively congested structure of 15a with the additional presence of a bulky OTBS. To overcome this obstacle, we turned to examine the catalytic efficiency of phosphinamide-derived palladacycle 18 , which was developed in our previous studies toward synthesizing P-stereogenic compounds through C–H arylation of phosphinamide 32 , 33 and exhibited excellent catalytic activity for Suzuki cross-coupling of aryl (pseudo)halides under mild conditions 34 . To our delight, we found that the palladacycle 18 did display high catalytic activity for such a heavily substituted nonactivated triflate 15a .…”
Section: Resultsmentioning
confidence: 99%
“…1 2-(3,5-Difluorophenyl)naphthalene (3u). 25 White solid (36 mg, 75%); mp 118.5−119.6 °C. Petroleum ether.…”
Section: -(Naphthalen-2-yl)benzo[d]mentioning
confidence: 99%